Dissipation and Residue of Chloroisobromine Cyanuric Acid in Ginger and Pepper and Its Dietary Intake Risk Assessment - Yadong Hao; Yingxuan Li; Jue Wang; Sen Pang; Shuang Li (Foods, 2024)
Chloroisobromine cyanuric acid is a highly effective broad-spectrum systemic fungicide for disease control in agricultural crops. In this study, the degradation, residue levels, and potential dietary risks associated with the chloroisobromine cyanuric acid residues in two widely consumed crops, pepper and ginger, were evaluated through supervised field experiments conducted at 12 sites for pepper and 4 sites for ginger in China in 2021. A QuEChERS-LC-MS/MS method was established for quantifying cyanuric acid (CYA) in both crops. The method achieved a limit of quantification (LOQ) of 0.02 mg kg−1 for ginger and 0.05 mg kg−1 for pepper, with recovery rates ranging from 91% to 96% for ginger and 84% to 89% for pepper and the relative standard deviation of 2.9% to 11.2% for ginger and 2.8%~12.9% for pepper, respectively. The results indicated that CYA had half-lives ranging from 3.1 to 8.2 days in pepper, and the terminal CYA residues at harvest were all lower than 5 mg kg−1, the maximum residue limit established in China. Furthermore, the chronic dietary risk exposure to chloroisobromine cyanuric acid in ginger and pepper, harvested at a pre-harvest interval of three days and at the normal harvesting time after the application of 50% chloroisobromine cyanuric acid soluble powder (SP), was 37.96%, which was much lower than 100%, indicating no significant health risks to the Chinese population. This study provides basic data for establishing the MRLs and serving as a reference for developing the analytical method applicable to CYA residues in different plant matrices.